Analisis Framing Mantan Koruptor Bakal Calon Legislatif Pemilu 2024 Pada cnn.indonesia.com - Tiara Ilmiwati Putri; Agus Machfud Fauzi; putri, tiara ilmiwati (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study analyzes the framing of news regarding former corruption convicts as legislative candidates in the 2024 General Election on CNN Indonesia. The Supreme Court decision that allows former corruption convicts to run for legislative office has sparked controversy related to election integrity and moral standards of political leadership. This research aims to identify how CNN Indonesia constructs this issue through news framing using Robert N. Entman's model which consists of four elements: define problems, diagnose causes, make moral judgments, and suggest remedies. The research employs a qualitative descriptive method with a constructivist paradigm, analyzing three news articles published on August 22, 2022, through documentation techniques and systematic text coding. The findings reveal that CNN Indonesia consistently frames the Supreme Court's decision as a threat to democratic integrity by defining the issue as a moral problem and election quality risk, attributing the cause of controversy to the Supreme Court through regulatory contradictions, applying dominant negative moral evaluations considering the ineligibility of former corruption convicts without exploring alternative perspectives, and implicitly recommending solutions through regulatory reform and strengthening public selectivity. The framing pattern reflects CNN Indonesia's ideological position that prioritizes election integrity and leadership moral standards, positioning the media as a moral agent reinforcing anti-corruption norms in public discourse. This study contributes to understanding how Indonesian mass media construct political discourse about integrity and eligibility of public leader candidates in the context of electoral democracy still facing systemic corruption challenges.